''Inciting the roughs of the crowd': soccer hooliganism in the south of Ireland during the inter-war period, 1919–1939'. (19th September 2017) - Tynan, Mark
Abstract : Hooliganism is not a term readily associated with soccer during the early twentieth century, nor is it a term commonly associated with the sport in Ireland. As such it may come as a surprise to note that the term was in circulation in Ireland during the inter-war period. This article begins by challenging the perception that the soccer-related violence that occurred in Ireland against the backdrop of the Anglo-Irish War (1919–1921) was solely a by-product of sectarian division in the north of the country. During this period violence around soccer was arguably just as prevalent, if less serious, in the south of Ireland, and the article describes how this violence persisted in the south into the 1920s and the 1930s. Finally, the article attempts to identify the root causes of soccer hooliganism in inter-war Ireland by analysing the violence in the context of the wider socio-economic environment.